MISSED NUTRITIONAL APPOINTMENTS IN PRIMARY HEALTH CARE - Sobrinho, Alairdson Rodrigues; Milane, Nayara Cristina (Cadernos ESP, 2026)
Absenteeism in nutritional consultations within Primary Health Care affects continuity of care and service efficiency. This study aimed to analyze rates of missed nutritional appointments at a Basic Health Unit in a municipality in Paraná, Brazil, from February to June 2025. This quantitative, descriptive study used secondary data on scheduled and completed consultations. Of 176 appointments, 63.6% were attended and 36.4% were missed, mostly follow-up visits. The findings highlight the need for strategies to reduce missed appointments, such as teleconsultations, automated reminders, and advanced-access scheduling. These measures can optimize resources, strengthen patient engagement, and improve health outcomes. Further multicenter and qualitative studies are recommended to explore factors associated with absenteeism and evaluate the effectiveness of proposed interventions.
Keywords: Public Health; Food; Diet and Nutrition; Absenteeism